2001
DOI: 10.3168/jds.s0022-0302(01)74500-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Dietary Biotin on Performance of Holstein Cows During Early Lactation

Abstract: This study determined the effects of supplemental dietary biotin (0, 10, or 20 mg/d) on performance of Holstein cows (n = 45; 18 primiparous and 27 multiparous). Treatments started at 14 d prepartum and continued until 100 d in milk (DIM). Blood samples were taken at 14 d prepartum, and blood and milk samples were taken at calving, and 30, 60, and 100 DIM. Dry matter intake during lactation was not different across treatments (19.7 kg/d). Milk production linearly increased with biotin supplementation (36.9, 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
93
12
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(140 citation statements)
references
References 16 publications
20
93
12
15
Order By: Relevance
“…They were similar to those observed by Zimmerly and Weiss (2001) in dairy cows at 110 d of lactation fed a diet with 46% forages, a level intermediate between those used in the present experiment.…”
Section: Plasma Variablessupporting
confidence: 91%
“…They were similar to those observed by Zimmerly and Weiss (2001) in dairy cows at 110 d of lactation fed a diet with 46% forages, a level intermediate between those used in the present experiment.…”
Section: Plasma Variablessupporting
confidence: 91%
“…However, apart from numerical increases in net acetate, i-valerate and total VFA release by the PDV, there was no evidence that feeding biotin altered rumen or post-rumen fermentation. Similarly, there was no effect of feeding biotin on rumen VFA proportions (Zimmerly and Weiss, 2001) or total tract fibre digestion (Majee et al, 2003).…”
Section: Volatile Fatty Acid Metabolismmentioning
confidence: 89%
“…Therefore, DM offered was restricted to just below ad libitum and not altered over the course of the study to reduce variation in nutrient absorption and metabolism by splanchnic tissues attributable to DMI. In dairy cows fed ad libitum, supplemental biotin has typically increased milk yield (Bonomi et al, 1996;Midla et al, 1998;Zimmerly and Weiss, 2001;Bergsten et al, 2003;Majee et al, 2003) but the effect has not been observed in every study reported (Fitzgerald et al, 2000;Rosendo et al, 2004). In the present study, the lack of a milk yield response to supplemental biotin may have been due to the restricted DMI of the cows, or the length of supplementation (14 days) may have been too short to allow for effects on milk yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations